Feasibility of three dimensional power Doppler ultrasonography methods to assess placental perfusion. (November 2020) - Schiffer, V.M.M.M.; Pellaers, D.; Hoenen, J.L.J.M.; van Kuijk, S.M.J.; Spaanderman, M.E.A.; Al-Nasiry, S.
Abstract: Objectives: Given the crucial role of the placenta in establishing a healthy pregnancy, reliable non-invasive methods to measure placental perfusion are desirable. The aim of this study is to determine the reproducibility and potential bias in different three-dimensional power Doppler (3DPD) methods assessing placenta perfusion. Methods: Ten singleton pregnancies around 16 weeks of gestation, with an anteriorly located placenta and centrally inserted umbilical cord were included in this study. Eight different combinations of a specific placental sweep and sonobiopsy method were used to evaluate placental perfusion. Vascularization index (VI), flow index (FI) and vascularization-flow index (VFI) were determined offline using the 4D-view program. Reproducibility and repeatability of the methods, expressed as correlation coefficients and Bland-Altman mean differences, were calculated. Differences between sampling methods were analyzed using t -test or Mann-Whitney U test. Results: Intra- and inter-class correlation coefficient (CC) was highest when using a spherical centrally placed sonobiopsy of 2 cm 3 in a whole placenta sweep (method 1; IntraCC VI 0.985, FI 0.769, VFI 0.993, InterCC VI 0.986, FI 0.784, VFI 0.987). Overall, intraCCs were higher compared to interCCs. Lowest mean differences in VI and FI were found comparing spherical to manual sonobiopsies, whereas the mean differences in VFI were lowest when comparing central versus peripheral located sonobiopsies. Comparing the three vascular indices, best median intra- and interCC and lowest mean differences were found for VFI. Conclusions: Three dimensional placental vascularization analysis showed best reproducibility using whole placental sweep volume and centrally located, spherical sonobiopsy of 2 cm 3 .